Cultivation of selected green algae for biomass and remediation of palm oil mill effluent (POME) - Mohammad Navid, Wais (2022)
The palm oil industry in Malaysia is one of the key players in contributing to the economy of the country. One of the major byproducts of the oil extraction process is the palm oil mill effluent (POME) and must undergo mandatory treatment before releasing the waste near rivers or water bodies. Studies on the remediation treatments is essential to prevent contamination to the surrounding aquatic environments. A massive amount of (POME) released from the industry is an ideal source of nutrients to cultivate micro and macroalgae. Micro and macroalgae are unicellular photosynthetic organisms that have the capability to reduce and assimilate contamination from wastewater and produce yield biomass for industrial applications. Therefore, this study aimed, to culture micro and macroalgae in different concentrations of POME (20%, 40%, 60%, and 80%) for microalgae and (5%, 10%, 15%, and 20%) for macroalgae as biological treatment. Furthermore, the species of micro and macroalgae were identified using microscopic and 18S rRNA gene sequences. The two species of microalgae (Chlorella vulgaris, Tetradesmus bernardii), mixed microalgae and macroalgae Pithophora roettleri were chosen for this research study. All the cultivation for micro and macroalgae were carried out in 250mL Erlenmeyer flasks containing 200mL medium with continuously light illumination 2000 Lux, pH 7-7.8, and room temperature of 25±1℃ for 21 days. The results showed positive effects on the growth, biomass production with 20% POME was optimal concentration for microalgae and 10% POME for macroalgae. Mixed microalgae revealed the highest growth rate with a mean value of (1.8677 ± 0.0560), followed by Chlorella vulgaris (1.7960 ± 0.0773) and Tetradesmus bernardii (1.7607 ± 0.0290). The lowest growth was found in 80% POME for Tetradesmus bernardii with a mean value of (0.7970 ± 0.2358) followed by Chlorella vulgaris (0.8927 ± 0.0363) and mixed microalgae (1.0413 ± 0.0644) respectively. And the highest biomass productivity was observed in 20% POME for mixed microalgae (with a mean value of 0.1733 ± 0.0057), followed by Chlorella vulgaris (0.1633 ± 0.0057) and Tetradesmus bernardii (0.1603 ± 0.0020). The lowest biomass was found in 80% POME for Tetradesmus bernardii (with a mean value of 0.0407 ± 0.0045) followed by Chlorella vulgaris (0.0447 ± 0.0055) and mixed microalgae (0.0440 ± 0.0.0069), and for macroalgae, the highest biomass (fresh weight) was observed in 10% POME with a mean value of (0.8903 ± 0.0237). The lowest biomass (fresh weight) was found in 20% (with a mean value of 0.5417±0.0124). Similarly, the highest nutrient removal (COD, TN, TP, N, P, and NH4) was observed in 20% POME for mixed microalgae with the highest percentage of COD (66%), TN (86%), TP (68%), N (80%), and P (64%) and lowest (in 80% POME) for COD (13%), TN (20%), TP (18%), N (29%), and P (31%). This is followed by Chlorella vulgaris at 20% POME with the highest removal of COD (64%), TN (79%), TP (49), N (72%), and P (59%) and at 20% POME, the lowest removal of COD (12%), TN (17%), TP (13%), N (26%), and P(19%) respectively. Next is Tetradesmus bernardii at 20% POME with highest removal of COD (61%), TN (72%), TP (35%), N (62%), and P (53%), and at 80% POME, the lowest removal at for COD (13%), TN (8%), TP (8%), N (21), P (17%). Lastly for macroalgae at 20% POME with the highest percentage of removal COD (70%), TN (70%), TP (80%), N (81%), and P (72%) and at 80% POME for lowest removal COD (16%), TN (16%), TP (38%), N (31%), and P (22%) respectively. In the future, POME has the prospect of an alternative medium for the cultivation of micro and macroalgae to achieve yield biomass for future industrial applications.